Customer retention : atonement oriented recovery strategies in the retail banking industry in Malaysia - Yeop Yunus Nek Kamal, M Goury Arsalan, Abd Razak Ahmad Zainal Abidin, Md Latip Nor Azrin (Universiti Pendidikan Sultan Idris, 2017)
Customer retention : atonement oriented recovery strategies in the retail banking industry in Malaysia by Yeop Yunus Nek Kamal, M Goury Arsalan, Abd Razak Ahmad Zainal Abidin, Md Latip Nor Azrin,